2020
DOI: 10.3390/insects11120869
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Mitochondrial Genome of Four Hylicinae (Hemiptera: Cicadellidae): Structural Features and Phylogenetic Implications

Abstract: To reveal mtgenome characterizations and reconstruct phylogenetic relationships of Hylicinae, the complete mtgenomes of four hylicine species, including Nacolus tuberculatus, Hylica paradoxa, Balala fujiana, and Kalasha nativa, were sequenced and comparatively analyzed for the first time. We also carried out the richest (11) subfamily sampling of Cicadellidae to date, and reconstructed phylogenetic relationships of Membracoidea among 61 species based on three datasets using maximum likelihood and Bayesian infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
5
4
0
Order By: Relevance
“…This result confirms that Ledrinae is an ancient group of leafhoppers. This result is in agreement with that reported by Chen et al (2019), Wang et al (2019a) and Wang et al (2019b) and differs from that reported by Du, Dai & Dietrich (2017a), Du et al (2017b) and Tang, Huang & Zhang (2020). Moreover, Tang, Huang & Zhang (2020) -S7).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result confirms that Ledrinae is an ancient group of leafhoppers. This result is in agreement with that reported by Chen et al (2019), Wang et al (2019a) and Wang et al (2019b) and differs from that reported by Du, Dai & Dietrich (2017a), Du et al (2017b) and Tang, Huang & Zhang (2020). Moreover, Tang, Huang & Zhang (2020) -S7).…”
Section: Discussionsupporting
confidence: 91%
“…This result is in agreement with that reported by Chen et al (2019), Wang et al (2019a) and Wang et al (2019b) and differs from that reported by Du, Dai & Dietrich (2017a), Du et al (2017b) and Tang, Huang & Zhang (2020). Moreover, Tang, Huang & Zhang (2020) -S7). The phylogenetic results are different from those of similar recent studies, for which there are two possible reasons: (1) we included all 13 PCGs and 2 rRNA genes in the phylogenetic analysis, whereas previous studies included 13 PCGs or selected a small number of species;…”
Section: Discussionsupporting
confidence: 91%
“…This result is in agreement with that reported by Chen et al (2019) and Wang et al (2019a, b) and differs from that reported by Du et al (2017a, b) and (Tang et al, 2020). Moreover, Tang et al (2020) reported that there is a stable relationship between the subfamilies [(Coelidiinae + Iassinae) + Hylicinae]. The results of the present study do not show such phylogenetic relationships but rather indicate that Deltocephalinae and Hylicinae are sister groups (Figs.…”
Section: Discussionsupporting
confidence: 90%
“…This result confirms that Ledrinae is an ancient group of leafhoppers. This result is in agreement with that reported by Chen et al (2019) and Wang et al (2019a, b) and differs from that reported by Du et al (2017a, b) and (Tang et al, 2020). Moreover, Tang et al (2020) reported that there is a stable relationship between the subfamilies [(Coelidiinae + Iassinae) + Hylicinae].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, there were some kinds of unmatched base pairs (Figures 4 and 5). These two structural characteristics are also present in other leafhoppers [40,48,49,[66][67][68][69]. In the predicted secondary structure, the length of the anticodon loop of all tRNAs was highly conserved for 7 bp, compared to the variable sizes of the DHU and TΨC loops.…”
Section: Transfer and Ribosomal Rna Genesmentioning
confidence: 75%